Ensino remoto de História em tempos de pandemia Covid-19: um estudo de caso - Nunes, Thiago Ivan Freitas (2022)
In the year 2020, the outbreak of the COVID-19 pandemic occurred, causing the stoppage of various sectors of society, including education. There was a requirement for social distancing and, with that, the education needed to be adapted to remote learning and, to this end, schools reformulated the curriculum and implemented the use of platforms through technologies and physical deliverable activities to the families of students. The present investigation aims to analyze the possible reflections, difficulties and possibilities of remote History teaching in the different realities: private and public municipal network of Santa Maria, RS, in the period of 2020, based on the study of biographical and autobiographical narratives of teachers working in the final years of elementary school. The defined problem-question was: To what extent did the COVID-19 pandemic and the remote teaching modality raise new reflections, possibilities and challenges for History teaching and historical education, based on autobiographical narratives of history teachers? This analysis is justified by the need to rethink the teaching of History and the new didactic-methodological approaches necessary to fulfill the objectives of the discipline. The methodology used was a case study, through the application of a semistructured questionnaire as a strategy for the generation of biographical and autobiographical narratives of History teachers from public and private schools in Santa Maria, RS, working in 2020, in final years of elementary school and research participants. The teaching of History in the pandemic period proved to be very laborious and presented as difficulties: the remote pedagogical mediation, the absence of internet, equipment and platforms of wide access for teachers and students, the unpreparedness for the use of technologies, the absence of governmental policies that support the educational processes, besides evidencing the social differences. However, it showed the importance of the classroom school and of education in general as perceived by society, it transformed the teachers into more humanized professionals facing the realities observed, and, as a legacy, it left the appreciation of History as a reflective subject for the understanding of the reality experienced, that is, the development of historical consciousness.